Implementasi Kebijakan Manajemen Pelayanan Berbasis Online: (Studi di Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil) Kota Manado - Mais, Trisno (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The purpose of this study is to solve a number of problems in the era of the COVID pandemic related to online-based management. Specifically, the purpose of this study is to solve problems that are directly related to employee knowledge related to excellent public service, the availability of human resources (HR), infrastructure to support effective and efficient public services, standard operating procedures for online-based services. In addition, analyzing the interests of who is affected, what benefits are generated, the position of online-based management policy makers, and other matters related to online-based management policies. The research method used is qualitative research. The informants who were determined by purposive sampling were 10 people consisting of the Head of the Manado City Population and Civil Registration Service (Disdukcapil), the Disdukcapil Secretary, as well as from leadership elements and members of the Manado City DPRD, and 5 Manado City residents.